Functional auditory disorders - Baguley, D.M.; Cope, T.E.; McFerran, D.J. (Elsevier, 2016)
There are a number of auditory symptom syndromes that can develop without an organic basis. Some of these, such as nonorganic hearing loss, affect populations similar to those presenting with functional somatosensory and motor symptoms, while others, such as musical hallucination, affect populations with a significantly different demographic and require different treatment strategies. Many of these conditions owe their origin to measurably abnormal peripheral sensory pathology or brain network activity, but their pathological impact is often due, at least in part, to overamplification of the salience of these phenomena. For each syndrome, this chapter briefly outlines a definition, demographics, investigations, putative mechanisms, and treatment strategies. Consideration is given to what extent they can be considered to have a functional basis. Treatments are in many cases pragmatic and rudimentary, needing more work to be done in integrating insights from behavioral and cognitive psychology to auditory neuroscience. The audiology literature has historically equated the term functional with malingering, although this perception is, thankfully, slowly changing. These disorders transcend the disciplines of audiology, otorhinolaryngology, neurology and psychiatry, and a multidisciplinary approach is often rewarding.